2017
DOI: 10.1515/jpm-2016-0406
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth restriction and placental gene expression in severe preeclampsia, comparing early-onset and late-onset forms

Abstract: There are significant differences in placental gene expression between severe early- and late-onset preeclampsia when both are associated with intrauterine growth restriction. ABI3BP, C7, HLA-G and IL2RB might contribute to the development of early form of severe preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 42 publications
6
33
0
Order By: Relevance
“…In silico miR screening analysis identified miR-1301 to have a predicted binding site in this region ( Figure 5A). miR-1301 is known to be dysregulated in early-onset preeclampsia [28], similar to HLA-G [29]. This finding strengthened our assumption that HLA-G might be regulated by miR-1301.…”
Section: Mir-1301 Is Not Involved In Hla-g Regulationsupporting
confidence: 79%
“…In silico miR screening analysis identified miR-1301 to have a predicted binding site in this region ( Figure 5A). miR-1301 is known to be dysregulated in early-onset preeclampsia [28], similar to HLA-G [29]. This finding strengthened our assumption that HLA-G might be regulated by miR-1301.…”
Section: Mir-1301 Is Not Involved In Hla-g Regulationsupporting
confidence: 79%
“…IPA of our data revealed that more than 50 pathways were disrupted in the first-trimester placenta derived from IVF-ET. Further analysis showed that these pathways are widely involved in key events of early placental development and function, whose disruption can lead to adverse outcomes [47][48][49]. We report the enrichment of multiple genes in the top 50 significantly overrepresented biological pathways.…”
Section: Discussionmentioning
confidence: 74%
“…Kim et al found that with the growth of the adult myocardium, the expression of WEE1 did not change but that expression inhibition occurred as a result of myocardial ischemia and hypoxic damage and further activated the functional activity of cyclin [ 24 , 26 ]. KRBOX1-AS1 is a recently discovered lncRNA, and its function has been mainly reported to be associated with to the early development of severe early-onset eclampsia and preoperative chemotherapy responses in locally advanced rectal cancer [ 27 , 28 ]. Ha et al found that the KRBOX1-AS1 has been reported to play a key role in the proliferation and apoptosis of rectal cancer cells and thus affects preoperative radiation therapy in rectal cancer patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%